Measurement of radiation dose in multi-slice computed tomography - Maharjan, Surendra; Prajapati, Sudil; Panta, Om Biju (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
The aim of this study was to measure the radiation doses for computed tomography (CT) examinations of the head, chest and abdomen in adult patients in Nepal in comparison to international standard. Dose length products (DLP) and effective doses for standard patient sizes were calculated from the reported volume CT dose index (CTDIVol). Details were obtained from approximately 90 CT examinations carried out in 128 slice CT scan. Effective dose was calculated for each examination using CT dose indices, exposure related parameters and CTDI-to-effective dose conversion factors. The CTDI and DLP were below the established international reference dose levels for head and chest while for the abdomen and pelvis, the CTDl and DLP were above the established international reference dose levels. The mean effective doses in this study for the head, chest, and abdomen were 1.7, 5.4 and 17.7 mGy respectively. In conclusion, for the routine head and chest protocol, CTDI, DLP and ED were found to be significantly lower compared to the recommendation of European Commission. However, abdomen CT scans showed higher dose values because of multiple phase scans and longer scan lengths.